2008
DOI: 10.1002/crat.200800040
|View full text |Cite
|
Sign up to set email alerts
|

The crystallization of lysozyme in the system of ionic liquid [BMIm][BF4]‐water

Abstract: Lysozyme crystallization was conducted in the ionic liquid (IL) 1-butyl-3-methylimidizolium tetrafluoroborate ([BMIm][BF 4 ]) with different buffer/IL proportions. It was found that the addition of [BMIm][BF 4 ] could promote the crystallization process, during which more lager single crystals with controllable morphologies could be obtained due to the manageable crystal growth velocity. A probable explanation was proposed based on the influence of the ionic polarization and kinetics in the lysozyme crystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…They assumed the BF 4 − , the anion of ILs, adhered to the surface of the lysozyme crystal, which resulted in the obstruction of the crystal growth [20]. We presumed that the variation of crystal morphology of sucrose crystals precipitated under different ionic liquid conditions has similar aspects with the result reported by Li et al It could be concluded as such because the anion was the variable, and the cation was the control in this study.…”
Section: Intramolecular Intermolecular Periodic Bonds Chains (Pbcs)supporting
confidence: 78%
See 1 more Smart Citation
“…They assumed the BF 4 − , the anion of ILs, adhered to the surface of the lysozyme crystal, which resulted in the obstruction of the crystal growth [20]. We presumed that the variation of crystal morphology of sucrose crystals precipitated under different ionic liquid conditions has similar aspects with the result reported by Li et al It could be concluded as such because the anion was the variable, and the cation was the control in this study.…”
Section: Intramolecular Intermolecular Periodic Bonds Chains (Pbcs)supporting
confidence: 78%
“…They assumed the BF4 − , the anion of ILs, adhered to the surface of the lysozyme crystal, which resulted in the obstruction of the crystal growth [20]. We presumed that the variation of crystal morphology of sucrose crystals precipitated under different ionic liquid conditions has similar aspects with the result reported by Li As observed in Figures 3 and 4, crystals have similar structures, but different crystal morphologies; this is due to differences in the adhesion of additional solvent, impurities, additives, etc., to the crystal surface, or due to the differences in the supersaturation level [37].…”
Section: Intramolecular Intermolecular Periodic Bonds Chains (Pbcs)mentioning
confidence: 99%
“…However, the impact of ionic liquids on the crystallization process is more pronounced than for precipitation [92,94]. Several authors report on less crystal polymorphism and improved tolerance to concomitant impurities during crystallization [94][95][96][97][98][99].…”
Section: Protein Crystallizationmentioning
confidence: 99%
“…In recent years, there has been an increasing attention to the application of ionic liquids in different areas of the protein science 1 -from protein stability, [2][3][4][5] activity, [6][7][8] and extraction [9][10][11][12] to protein crystallization. [13][14][15][16][17][18][19][20] One of the reasons for this relevance is the tunable nature of ILs that allows tailoring ILs with specific chemical and physical properties. 21 In regard to protein crystallization, studies have mainly focused on model proteins in order to understand the origin of the ILs influence on biomacromolecular crystals formation.…”
Section: Introductionmentioning
confidence: 99%